2014
DOI: 10.1111/ped.12214
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition and obesity among cystic fibrosis patients

Abstract: Background: Optimal nutritional status (NS) in cystic fibrosis (CF) is associated with better lung function and increased overall survival. This study estimated the prevalence of malnutrition and obesity among CF patients in a tertiary center. Conclusions: Despite appropriate management only one-third of the present patients had optimal NS. One-fourth were malnourished and a significant percentage were overweight/obese. The latter were mostly carriers of mutations other than F508del and had better pulmonary fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 32 publications
5
27
1
1
Order By: Relevance
“…The patients with overweight or obesity were more likely to be older, pancreatic sufficient, have better pulmonary function, milder genotype and are less likely to be colonized. Similar results were presented from Greece, where despite increase of overweight or obesity, 22% of patients still showed malnutrition [83].…”
Section: Relation Obesity and Clinical Parameterssupporting
confidence: 87%
“…The patients with overweight or obesity were more likely to be older, pancreatic sufficient, have better pulmonary function, milder genotype and are less likely to be colonized. Similar results were presented from Greece, where despite increase of overweight or obesity, 22% of patients still showed malnutrition [83].…”
Section: Relation Obesity and Clinical Parameterssupporting
confidence: 87%
“…The S-K score was not used in three previous studies of the nutritional status in CF patients. (21)(22)(23) In contrast, there was no significant association between malnutrition and the S-K score in the study by Ziegler et al (24) Longitudinal studies have demonstrated that malnutrition can be expected to increase with aging. (31,32) However, it is interesting that our results showed that young age was a predictor of malnutrition only in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 88%
“…However, that study involved 37 children and adolescents. (21) In contrast, a study carried out in an adult tertiary CF center in France with 163 patients showed that 49.7% of the patients suffered from malnutrition. (22) That study also used the same methodology and the same cut-off points for classifying malnutrition.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…HAN et al [6] reported that adiposity indicators were associated with asthma in children with exhaled nitric oxide fraction (FeNO) as a biomarker of eosinophilic airway inflammation and that among children with asthma, adiposity was associated with worse asthma severity or control in those with high FeNO. In 2014, several studies also reported an increased prevalence of overweight and obesity in patients with CF even in those with pancreatic insufficiency [7][8][9][10]. Generally, however, overweight CF patients had milder genotypes and better lung function.…”
Section: Adiposity and Respiratory Disease Riskmentioning
confidence: 99%